Polymorphisms in Fatty Acid Desaturase (FADS) Gene Cluster: Effects on Glycemic Controls Following an Omega-3 Polyunsaturated Fatty Acids (PUFA) Supplementation - Patrick Couture (Genes, 2013)
Changes in desaturase activity are associated with insulin sensitivity and may be associated with type 2 diabetes mellitus (T2DM). Polymorphisms (SNPs) in the fatty acid desaturase (FADS) gene cluster have been associated with the homeostasis model assessment of insulin sensitivity (HOMA-IS) and serum fatty acid composition. Objective: To investigate whether common genetic variations in the FADS gene cluster influence fasting glucose (FG) and fasting insulin (FI) responses following a 6-week n-3 polyunsaturated fatty acids (PUFA) supplementation. Methods: 210 subjects completed a 2-week run-in period followed by a 6-week supplementation with 5 g/d of fish oil (providing 1.9 g–2.2 g of EPA + 1.1 g of DHA). Genotyping of 18 SNPs of the FADS gene cluster covering 90% of all common genetic variations (minor allele frequency ≥ 0.03) was performed. Results: Carriers of the minor allele for rs482548 (FADS2) had increased plasma FG levels after the n-3 PUFA supplementation in a model adjusted for FG levels at baseline, age, sex, and BMI. A significant genotype*supplementation interaction effect on FG levels was observed for rs482548 (p = 0.008). For FI levels, a genotype effect was observed with one SNP (rs174456). For HOMA-IS, several genotype*supplementation interaction effects were observed for rs7394871, rs174602, rs174570, rs7482316 and rs482548 (p = 0.03, p = 0.01, p = 0.03, p = 0.05 and p = 0.07; respectively). Conclusion: Results suggest that SNPs in the FADS gene cluster may modulate plasma FG, FI and HOMA-IS levels in response to n-3 PUFA supplementation.